Copper isotope fractionation in the Meiduk porphyry copper deposit, Northwest of Kerman Cenozoic magmatic arc, Iran. (3rd December 2014) - Asadi, Sina; Mathur, Ryan; Moore, Farid; Zarasvandi, Alireza
Abstract The Meiduk deposit possesses three different Cu reservoirs each with a unique Cu isotope signature. δ65Cu for the leached cap minerals ranges from −2.5 to +0.49‰ to −0.45 to +0.3‰ for hypogene minerals and from +1.3 to +4.4‰ for supergene enrichment minerals. Oxidation of hypogene sulphides and effective trapping of copper (from solutions derived from the leached cap) in the supergene enrichment zone caused this relationship. A systematic pattern of low Cu isotope values close to the surface and higher isotope values with depth reveals a palaeo‐fluid pathway in the northwest–southeast direction over the deposit. Thus, the copper isotope data from leached cap and enrichment minerals can be used to monitor copper migration during supergene weathering at the Meiduk deposit.